2012
DOI: 10.5588/ijtld.11.0116
|View full text |Cite
|
Sign up to set email alerts
|

Rise in rifampicin-monoresistant tuberculosis in Western Cape, South Africa

Abstract: SUMMARY SETTING Brewelskloof Hospital, Western Cape, South Africa. OBJECTIVES To verify the perceived increase in rifampicin monoresistant tuberculosis (RMR-TB) in the Cape Winelands-Overberg region and to identify potential risk factors. DESIGN A retrospective descriptive study of trends in RMR-TB over a 5-year period (2004–2008), followed by a case-control study of RMR and isoniazid (INH) monoresistant TB cases, diagnosed from April 2007 to March 2009, to assess for risk factors. RESULTS The total num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 17 publications
5
52
1
3
Order By: Relevance
“…More recently, an additional risk factor (excessive alcohol use) has been reported in surveys for Brazil, South Africa, Burundi, and Russia. [30][31][32][33] In the present study, 33.6% of RMR patients had a history of TB or had close contact with a known TB patient. This rate reached 58% in immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an additional risk factor (excessive alcohol use) has been reported in surveys for Brazil, South Africa, Burundi, and Russia. [30][31][32][33] In the present study, 33.6% of RMR patients had a history of TB or had close contact with a known TB patient. This rate reached 58% in immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of MDR-TB in Italy is low but has increased in recent years, possibly because of increased immigration from developing countries (22). It is well known that more than 90% of RIF resistance is associated with INH resistance (23); for this reason, RIF resistance is widely used by other commercial tests, such as the GeneXpert MTB/RIF assay, as a surrogate marker for MDR-TB (23). It was shown that a number of false-positive results for RIF resistance were detected with those assays, however, and the consequences were discussed from clinical and public health perspectives (24).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 285 smear-positive samples which were subjected to the LPA test, 41.5% were found susceptible to INH and RIF, while 22.2% samples showed RIF monoresistance, which can be expected in a high-TB-burden country like India (8,13). Much lower RIF monoresistance levels were reported from another high-TB-burden country (South Africa [13.5%]) and a low-TB-burden country (United States [13%]) (22,23). In the present study, high RIF resistance could be due to the fact that most of the samples were received from relapse cases, which were on category II treatment for more than 2 months.…”
Section: Discussionmentioning
confidence: 99%